Her Side of the Story: From the author of Forbidden Notebook - De Céspedes, Alba; Foulston, Jill (New York : Astra House, 2023)
"Set against the backdrop of fascist Rome, Her Side of the Story is a richly told novel about a woman driven to murder the man she loves"